2011
DOI: 10.1186/1756-3305-4-241
|View full text |Cite
|
Sign up to set email alerts
|

Topography as a modifier of breeding habitats and concurrent vulnerability to malaria risk in the western Kenya highlands

Abstract: BackgroundTopographic parameters such as elevation, slope, aspect, and ruggedness play an important role in malaria transmission in the highland areas. They affect biological systems, such as larval habitats presence and productivity for malaria mosquitoes. This study investigated whether the distribution of local spatial malaria vectors and risk of infection with malaria parasites in the highlands is related to topography.MethodsFour villages each measuring 9 Km2 lying between 1400-1700 m above sea level in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 20 publications
4
54
0
1
Order By: Relevance
“…There, the tremendous variations of malaria transmission intensity in a small spatial scale are caused by substantial differences in altitude, topography and other environmental conditions [6,7,21,22]. We now expand our antibody profiling survey to include 854 P. falciparum polypeptides by using protein microarray technology.…”
Section: Introductionmentioning
confidence: 99%
“…There, the tremendous variations of malaria transmission intensity in a small spatial scale are caused by substantial differences in altitude, topography and other environmental conditions [6,7,21,22]. We now expand our antibody profiling survey to include 854 P. falciparum polypeptides by using protein microarray technology.…”
Section: Introductionmentioning
confidence: 99%
“…The western Kenyan highlands is an area of unstable, sometimes epidemic malaria 34 where anopheline vector dynamics determine the spread and maintenance of malaria transmission. [35][36][37] The aim of our study was to identify Anopheles species present in two neighboring districts in the western Kenyan highlands using both molecular and morphological tools. This study expands upon previously reported findings of unknown and potentially new vector species in Kisii district, 38 detailing the rDNA ITS2 and mtDNA CO1 regions, and includes sequence analysis of two more recent sets of mosquito collections from an area in the neighboring district, Rachuonyo South.…”
Section: Introductionmentioning
confidence: 99%
“…Topographical attributes are potentially relevant for habitat suitability of malaria vectors, thus, aspect, slope, and elevation were extracted from the DEM. 13,18 The aspect, which ranges from 0 to 360 degrees, was categorized into three topographically important slope orientations: north-facing, south-facing, and all other slope orientations. In the southern hemisphere, north-facing slopes tend to be warmer and less humid because of more direct sunlight.…”
Section: Methodsmentioning
confidence: 99%